Reduction of Linear Equation in Different Forms | kullabs.com
Notes, Exercises, Videos, Tests and Things to Remember on Reduction of Linear Equation in Different Forms

Please scroll down to get to the study materials.

Registration open for Special Discounts

Note on Reduction of Linear Equation in Different Forms

Registration open for Mr and Miss SEE
  • Note
  • Things to remember
  • Videos
  • Exercise
  • Quiz

Linear Equation Ax + By + C = 0

Linear Equation
Linear Equation
Source:nordenergi.org

An equation between any two variables which straight line on a graph is known as a linear equation. In this equation, Ax + By + C = 0, where A, B, and C are neutrals and also A and B will not be together zero.
To prove this statement, let P(x1, y1), Q(x2, y2) and R(x3, y3) be nay three points on the locus represent by the equation Ax + By + C = 0. The coordinates of the points must satisfy the equation.
Hence,
Ax1 + By1 + C = 0 . . . . . . . . . . . . . . (i)
Ax2 + By2 + C = 0 . . . . . . . . . . . . . . (ii)
Ax3 + By3 + C = 0 . . . . . . . . . . . . . . (iii)
Solving first two equations by the rule of cross multiplication, we get
\(\frac{A}{y_1 - y_2}\) = \(\frac{B}{x_1 - x_2}\) = \(\frac{C}{x_1 y_2 - x_2 y_1}\) = k (say)
∴ A = k(y1 - y2), B = k(x2 - x1) and C = k(x1y2 - x2y1)
Substituting the values of A, B and C in the third equation, we get
k(y1 - y2) x3 +k(x2 - x1) y3 + k(x1y2 - x2y1) = 0
or, k(x3y1 - x3y2 + x2y3 - x1y3 + x1y2 - x2y1) = 0
or, x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3 = 0
Multiplying both sides by \(\frac{1}{2}\), we get
\(\frac{1}{2}\)(x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3) = 0
i.e. Area of ΔPQR = 0
This result sgows us that the points P, Q and R are collinear.
Thus, the general equation of first degree in x and y always represents a straight line.

Reduction of general equation of first degree to the three standard forms

There is three standard form to reduce the linear equation. They are given below:

Reduction to the slope intercept form
The first-degree general equation in x and y is
Ax + By + C = 0
This equation can be writtenas
By = -Ax - C
or, y = (-\(\frac{A}{B}\))x + (-\(\frac{C}{B}\)) which is of the form y = mx + c where
slope (m) = -\(\frac{A}{B}\) = -\(\frac{coefficient \: of \: x}{coefficient \: of \: y}\) and
Y-intercept (c) = -\(\frac{C}{B}\) = -\(\frac{content \: term}{coefficient \: of \: B}\)

Reduction of the double intercept form
The first-degree general equation in x and y is
Ax + By + C = 0
This equation can be writtenas
Ax + By = -C
Dividing both sides by -C, we get
\(\frac{Ax}{-C}\) + \(\frac{By }{-C}\) = 1
or, \(\frac{x}{\frac{-C}{A}}\) + \(\frac{y}{\frac{-C}{B}}\)= 1 which is of the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1 where
X-interccept (a) = -\(\frac{C}{A}\) = -\(\frac{constant \: term}{coefficient \: of \: x}\)
Y-intercept (b) = -\(\frac{C}{B}\) = -\(\frac{constant \: term}{coefficient \: of \: y}\)

Reduction to the normal form
The equation Ax + By + C = 0 and x cosα = p will represent one and ssame straight line if their corresponding coefficients are proportional.
∴ \(\frac{cosα}{A}\) = \(\frac{sinα}{B}\) = \(\frac{-p}{C}\) = k (say)
Then, cosα = Ak, sinα = Bk and -p = Ck
Now,
(Ak)2 + (Bk)2 = cos2α + sin2α = 1
or, k2 (A2 + B2) = 1
or, k= \(\frac{1}{A^2 + B^2}\)
or, k = ± \(\frac{1}{\sqrt{A^2 + B^2}}\)
∴ cosα = \(\frac{A}{±\sqrt{A^2 + B^2}}\), sinα = \(\frac{B}{±\sqrt{A^2 + B^2}}\) and p = \(\frac{-C}{±\sqrt{A^2 + B^2}}\)
Hence, the normal form is \(\frac{A}{±\sqrt{A^2 + B^2}}\)x + \(\frac{B}{±\sqrt{A^2 + B^2}}\)y = \(\frac{-C}{±\sqrt{A^2 + B^2}}\)
The + or - sign in the RHS being so chosen as to make the RHS positive.

Length of the perpendicular from a point on a straight line

To find the length of the perpendicular from a point on the line x cosα + y sinα = p


Let the equation of a line AB be x cosα + y sinα = p.
Then the length of a perpendicular from the origin on the line is p.
i.e. ON = p and∠AON =α
Let P(x1, y1) be any point and draw perpendicular PM from P to the line AB.
Through the point P, draw a line CD parallel to the given line AB. Let ON' be the perpendicular drawn from the origin to the CD such that ON' = p'.
Then,
PM = ON' - ON' = p' - p when p' > p and PM = ON - ON' = p - p' when p> p'.
Thus, PM = ± (p' - p). Here, the proper sign is taken so as make PM positive.
Now equation of CD is x cosα + y sinα = p'
But this line passes through the point (x1, x1)
So, x1 cosα + y1 sinα = p'
Hence, PM = ± (x1 cosα + y1 sinα - p) which is the length of the perpendicular drawn from (x1, y1) on the line x cosα + y sinα = p.

To find the length of the perpendicular from a point on the line Ax + By + C = 0
Here, the general equation of the first degree in x and y in Ax + By + C = 0.
Changing the equation into perpendicular form we get,
\(\frac{A}{\sqrt{A^2 + B^2}}\)x + \(\frac{B}{\sqrt{A^2 + B^2}}\)y + \(\frac{C}{\sqrt{A^2 + B^2}}\) = 0
Comparing this equation with x cosα + y sinα - p = 0 we get,
cosα = \(\frac{A}{\sqrt{A^2 + B^2}}\), sinα =\(\frac{B}{\sqrt{A^2 + B^2}}\) and p = -\(\frac{C}{\sqrt{A^2 + B^2}}\)
Now, length of the perpendicular drawn from the point (x1, y1) to the line x cosα + y sinα - p is

L = ± (x1 cosα +y1 sinα - p)

= ± (x1\(\frac{A}{\sqrt{A^2 + B^2}}\) + y1\(\frac{B}{\sqrt{A^2 + B^2}}\) -\(\frac{C}{\sqrt{A^2 + B^2}}\))

= ± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))

Hence, length of the perpendicular drawn from the point (x1, y1) to the line
Ax + By + C = 0 is ± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))

 

  1. An equation between any two variables which straight line on a graph is known as a linear equation. In this equation, Ax + By + C = 0, where A, B, and C are neutrals and also A and B will not be together zero.
  2. Ax + By + C = 0 is± (\(\frac{Ax_1 + By_1 + C}{\sqrt{A^2 + B^2}}\))
  3. Ax + By + C = 0
  4. \(\frac{1}{2}\)(x1y2 - x2y1 + x2y3 - x3y2+ x3y1 - x1y3) = 0
.

Very Short Questions

Solution:

Here, 
3x + 4y + 5 = 0 
Reduce it into slope intercept from, 4y = -3x - 5 
or, y = \(\frac{-3}{4}\) x - \(\frac{5}{4}\)
which is in the form y = mx + c, 
so, on comparing, we get,
Slope (m) = \(\frac{-3}{4}\) and 
y-intercept (c) = \(\frac{-5}{4}\)

Solution:

Here, 
4x + 5y + 20 = 0 
or, \(\frac{4x}{-20}\) + \(\frac{5y}{-20}\) = 1
or, \(\frac{x}{-20/4}\) + \(\frac{y}{-20/5}\)
or, \(\frac{x}{-5}\) + \(\frac{y}{-4}\) = 1 
which is in the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1,
∴ x-intercept (a) = -5 and y-intercept (b) = -4

Solution:

Here, 
2x + 5y - 20 = 0 
or, 2x + 5y = 20 
or, \(\frac{2x}{20}\) + \(\frac{5y}{20}\) = 1 
or, \(\frac{x}{10}\) + \(\frac{y}{4}\) = 1 
Which is in the form \(\frac{x}{a}\) + \(\frac{y}{b}\) = 1
∴ X-intercept (a) = 10
y-intercept (b) = 4 
∴ Area of ΔAOB = \(\frac{1}{2}\) OA × OB 
= \(\frac{1}{2}\) × 10 × 4 
= 20 sq. units

Solution:

The equation of line is 3x + 4y + 7 = 0 
Perpendicular length (p) = |\(\frac{ax_1 + by_1 + c}{\sqrt{a^2 + b^2}}\)|

we have, (x1,y1)= (-3,0)

So, p =  |\(\frac{3\times(-3)+ 4\times 0}{\sqrt{3^2 + 4^2}}\)|= \(\frac{9}{5}\)

Solution:

The equation of line is 3x + 4y + 7 = 0 
Perpendicular length (p) =\(\vert \frac{ax_1+by_1+c}{\sqrt{a^2+b^2}}\vert\)
Where (x1 , y1) is the point from whhich the perpendicular is drawn on the line 
or, p = \(\vert\frac{3 . (-3) + 4 . 0 + 7}{\sqrt{(3)^2 + (4)^2}}\vert\)
or, p = \(\vert\frac{-9 + 7}{\sqrt{9 + 16}}\vert\)
or, p = \(\vert\frac{-2}{5}\vert\)
∴ p = \(\frac{2}{5}\) units

0%
  • Find the length of the perpendicular drawn from (0,0) to the line 2x +3y+5=0.

    (frac {8}{sqrt{29}})    
    (frac {2}{sqrt{30}})
    (frac {5}{sqrt{13}})  
    (frac {8}{sqrt{29}})  
  • Find the length of perpendicular drawn from(1,2) to the line 2x + 5y -20=0

    (frac {6}{sqrt{29}})
    (frac {9}{sqrt{29}})
    (frac {2}{sqrt{29}})
    (frac {8}{sqrt{29}})
  • Find the perpendicular drawn from (-2, 5) to the line x +y -5=0

    (sqrt {5})
    (sqrt {2})
    (sqrt {4})
    (sqrt {3})
  • Find the perpendicular drawn from(3, -2) to the line x - y- 6 = 0

    (frac {3}{sqrt{2}})
    (frac {1}{sqrt{3}})
    (frac {2}{sqrt{4}})
    (frac {1}{sqrt{2}})
  • Find the perpendicular drawn from(-7, -2) to the line 6x -8y- 20 = 0

    (frac {23}{5})
    (frac {24}{8})
    (frac {25}{2})
    (frac {21}{5})
  • find the distance between the parallel lines 3x +  5y = 11 and 3x +5y =-23

    (frac {13}{sqrt{35}})
    (frac {10}{sqrt{34}})
    (frac {11}{sqrt{34}})
    (frac {12}{sqrt{34}})
  • find the distance between the parallel line 2x - y + 5 = 0 and 6x  -3y +20 = 0

    (frac {sqrt5}{3})
  • find the distance between the parallel line x+2y - 1 = and 5x + 10y + 7 = 0

    (frac {2}{5sqrt{5}})
    (frac {2}{5sqrt{8}})
    (frac {2}{5sqrt{6}})
    (frac {2}{5sqrt{7}})
  • The straight line 4x  + 5y  -20 = 0 cuts  X- axis at A and Y axis at B. find X-intercept, Y-intercept hence find the area of ( riangle)AOB. 

    10 sq. units
    ;i:3;s:18:
    12 sq. units 
  • The  line 4x  - y  +16 = 0 cuts  X- axis at P and Y axis at Q. find the area of ( riangle) POQ

    32 sq. units 
    31 sq. units 
    33 sq. units 
    34sq. units 
  • You scored /10


    Take test again

DISCUSSIONS ABOUT THIS NOTE

You must login to reply

Forum Time Replies Report
shankar

how to find two lines are parallel


You must login to reply